Public Employment Labor Relations : An Overview of Eleven Nations - Boivin, Jean (Relations industrielles / Industrial Relations, 1976)
This article reviews "Public Employment Labor Relations : An Overview of Eleven Nations" edited by Charles M. Rehmus.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z